Virtual Training for Managing Emerging Zoonotic Diseases including COVID-19 - Ramjee P Ghimire; Karim M Maredia; Melinda J. Wilkins (Journal of International Agricultural and Extension Education, 2022)
The burden of zoonotic diseases is an important global issue affecting human and animal health, food value chains, international trade, and the environment. Two-thirds of the infectious diseases affecting human health are of animal origin. Information and knowledge of zoonotic diseases and associated effects is critical for managing these diseases. The World TAP at Michigan State University offered an online course in zoonotic diseases in March 2021, which a diverse group of 42 participants from 15 countries in Africa, Asia, Middle East, and Americas attended. Grounded on Experiential Leaning Theory this paper discusses the conceptualization, design, implementation, outcomes of, and lessons-learned from this course. Key contents of this comprehensive course included epidemiology of zoonotic diseases, zoonoses of wildlife origin, utilizing a One Health approach to managing zoonoses, and roles of regional/international organizations in strengthening zoonotic disease management capacities, and the lessons-learned from the pandemic on diagnosis, prevention, and prediction of zoonotic diseases. The paired t-test results using pre- and post-course survey data showed significant increases in the participants’ level of knowledge on zoonoses post-course. in comparison to their pre-course knowledge. During the interactive discussion, participants stressed the need for continuing information sharing, and networking. For future offerings, the participants suggested adding impacts of zoonoses on international trade, and effect of climate change on zoonoses., and increasing collaborations between national, regional, and international organizations working on zoonoses. With the success of the first offering, MSU will continue to offer this course in the future, may be in a hybrid mode.
Keywords: zoonotic diseases; training; capacity building; online course; experiential learning cycle